Studi Karakteristik Tipe Diabetes pada Tikus (Rattus novergicus) yang Diinduksi Deksametason (CHARACTERISTIC STUDY OF THE TYPE OF DIABETES IN RAT (RATTUS NOVERGICUS) MODEL INDUCED BY DEXAMETHASONE) - Hanim, Rahmania; Darusman, Huda Shalahudin; Rahminiwati, Min (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Diabetes is marked by hyperglicemia with severe symptoms included polydipsi, polyuri, polyphagia,weight loss, and decreased of insulin sensitivity index specially at type 2 diabetes mellitus. The objective of this research was to analyze the characteristics of diabetes mellitus in rat  (Rattus novergicus) which induced by dexamethason. A total of 24 rats were divided into four groups which divided as follow: (1) aquabidest subcutaneously (K0), (2) subcutaneous dexamethasone 1 mg/kgBW daily (K1), (3) subcutaneous dexamethasone 2.5 mg/kgBW daily (K2) and subcutaneous dexamethasone 5 mg/kgBW daily (K3). The data of fasting blood glucose, fasting blood insulin, body weight and feed intake, urine volume and water intake collected at day 0, 5, 10 and 15 (five days after the last treatment). The result showed that there was a significant elevation of glucose level followed by significant decreased of insulin sensitivity index and the body weight of rats in group wich induced by dexamethasone but there was no change in feed intake, water intake, volume of urine and fasting blood insulin before and after the treatment. There was insignificant different of total beta pancreatic islet between treatment and control grup. Induction of dexamethasone in mice causes reversible hyperglycemia and has not met the characterisics of either type 1 or 2 diabetes mellitus models. The profile of dexamethasone induced diabetes model has their own spesific type.
Keywords: Dexamethasone, insulin sensitivity index, beta pancreatic cells, hyperglycemia